PERSPEKTIF WAJIB PAJAK USAHA MIKRO KECIL DAN MENENGAH TENTANG MAKNA PAJAK DAN IMPLIKASINYA - Tri Widodo, Ardi; Hidayatulloh, Amir (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to determine the meaning of tax and its implications from the perspective of the UMKM taxpayers. Design/methodology/approach- Qualitative research with the object of research is the MSME entrepreneurs in the city of Yogyakarta, totaling three sources. Findings- The results of the study confirm that the UMKM taxpayers have interpreted tax in accordance with Law Number 28 of 2007. UMKM taxpayers interpret tax as a reward for income and obligations. Implication- Based on the results of the research, the government is required to be consistent with the policies that have been determined, especially regarding taxation, and to provide comprehensive socialization on taxation to all levels of society, especially MSME players. Changes in policy that are not followed by equal outreach, can lead to misunderstanding for taxpayers because they cannot implement or follow policies properly. Keywords: SMEs, Tax